Razi on human needs: Conception and further reflections - Mohd. Nor, Hanapi (2012)
Fakhr al-Din al-Rāzi (606 HE/1149-1209 CE) is one of the greatest scholars after Ghazāli. This poster presentation has a single primary objective, i.e. to high-light the Islamic intellectual heritage on human needs and well-being which is relevant to the contemporary Muslim ummah situation. In determining which of Rāzi's statements are relevant to our ummah present predicaments, we examine two different disciplines which are inter-related: (1) Humanistic views represented by Abraham Maslow, and (2) economic neoclassical as has been carried out world-wide by the neo-liberalism. The presentation concludes that any fundamental human needs not adequately satisfied generates a pathological conditions, physically or psychologically or even both. Rāzi's theory is based on the ultimate origin of human needs. The fulfillment of which will secure one temporal or psycho-physical and social needs. Thus, in turn will guarantee his or her well-being (al-falah, al-najat).